The substrate effect on mechanical, adhesion and tribological properties of CrCN films deposited by magnetron sputtering. (23rd December 2020) - Keles, Aysenur
Thin film is an application that only improves surface properties without changing the properties of material. Transition metal nitrides are used in many areas. CrCN films are metal nitrides with superior properties. The adhesion is important for the performance of the part as it will affect the surface properties. Therefore, the effect of substrate, an important parameter, was investigated in this study. CrCN films were coated onto M2, 4140, 316L and Ti6Al4V substrates using the pulsed-dc power supply by CFUBMS technique. The microstructural properties of CrCN films were investigated using SEM. The phase orientation of CrCN films was determined by XRD. The elemental composition and binding energy of CrCN films were defined using XPS. A scratch tester was used to determine the adhesion between coating and substrate. Also, friction and wear properties were determined using a tribo-tester. The results showed that CrCN films had better adhesion to steel type substrates.